Testing which proposed regulations need ?competition-proofing? - Lyons, Sean (Statistical and Social Inquiry Society of Ireland, 2006)
When assessing the likely net impact of regulation, many jurisdictions test for specific effects on areas of concern, such as small businesses or the environment, as well as for more generalised costs and benefits. This paper considers how best to design a negative-clearance test for the competition effects of regulations. One such test, the well-documented UK ?competition filter?, has serious shortcomings. Important classes of potentially damaging measures will not trigger the UK filter, and we illustrate this by applying the filter to four controversial measures that are currently, or were recently, on the statute books in Ireland. Structural and other features of the UK filter that lead to these outcomes are identified. We then outline an alternative test structure that should reduce such ?false negatives? while remaining practical to apply.
Read before the Society, 26 January 2006
Keywords: Regulatory impact assessment; Cost-benefit analysis; Regulation; Competition; 314.15